2008
DOI: 10.1073/pnas.0800897105
|View full text |Cite|
|
Sign up to set email alerts
|

Organization of the core structure of the postsynaptic density

Abstract: Much is known about the composition and function of the postsynaptic density (PSD), but less is known about its molecular organization. We use EM tomography to delineate the organization of PSDs at glutamatergic synapses in rat hippocampal cultures. The core of the PSD is dominated by vertically oriented filaments, and ImmunoGold labeling shows that PSD-95 is a component of these filaments. Vertical filaments contact two types of transmembrane structures whose sizes and positions match those of glutamate recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
280
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 259 publications
(308 citation statements)
references
References 47 publications
25
280
0
3
Order By: Relevance
“…Using previous measurements of the number of PSD-95 molecules present at synapses (8,12) (see SI Text), we converted our imaging data into an estimate of the absolute density of PSD-95 molecules in the PSD. The results of this analysis predict a mean density of 4.3 Ϯ 0.4 PSD-95 molecules per 1000 nm 2 in the PSD, or a center-to-center spacing of 17 Ϯ 1 nm, remarkably consistent with the 10 nm size of purified PSD-95 (22) and the nearest-neighbor spacing of 13 nm measured by electron tomography (17), and supporting the notion of a dense arrangement of PSD-95 molecules capable of binding one another either directly or through minimal intermediates. Notably, the pattern of molecular density within PSDs changed over time, with localized concentration and dispersion of PSD-95 occurring within PSD subdomains over periods of minutes (Fig.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…Using previous measurements of the number of PSD-95 molecules present at synapses (8,12) (see SI Text), we converted our imaging data into an estimate of the absolute density of PSD-95 molecules in the PSD. The results of this analysis predict a mean density of 4.3 Ϯ 0.4 PSD-95 molecules per 1000 nm 2 in the PSD, or a center-to-center spacing of 17 Ϯ 1 nm, remarkably consistent with the 10 nm size of purified PSD-95 (22) and the nearest-neighbor spacing of 13 nm measured by electron tomography (17), and supporting the notion of a dense arrangement of PSD-95 molecules capable of binding one another either directly or through minimal intermediates. Notably, the pattern of molecular density within PSDs changed over time, with localized concentration and dispersion of PSD-95 occurring within PSD subdomains over periods of minutes (Fig.…”
Section: Resultssupporting
confidence: 60%
“…We reasoned that changes to the PSD itself are highly likely to reflect altered synapse function. PSD-95 is tightly associated with the membrane by N-terminal palmitoylation and by PDZ interactions with NMDA receptors, transmembrane AMPA receptor regulatory proteins (TARPs), and synaptic adhesion molecules (17,44,45). The deformation of the PSD that we have documented is thus likely accompanied by localized distortion of the postsynaptic membrane, the shape of the synaptic cleft, or the alignment of the presynaptic and postsynaptic membranes.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…New studies using superresolution light microscopy observed that AMPARs (21,22) and palmitoylated PSD95 (22,23) within PSDs were clustered in nanodomains. Using EM tomography, Chen et al (1,2) found NMDAR clusters were separate from AMPARs. The NMDAR nanodomain contained NMDAR-PSD95 complexes in a 1:2 stoichiometry, whereas other PSD regions with AMPARs contained AMPAR-PSD95 complexes in a 1:1 stoichiometry.…”
mentioning
confidence: 99%